Design/upgrade of a transparent optical network topology resilient to the simultaneous failure of its critical nodes - Barbosa, Fábio (2020)
This paper addresses two related problems in the context of transparent optical networks. In the network design problem, the aim is to identify a set of fiber links to connect a given set of nodes. In the network upgrade problem, the aim is to identify a set of new fiber links to add to a given network topology. For a given fiber length budget, the aim in both problems is to maximize the network resilience to the simultaneous failure of its critical nodes. The resilience is evaluated by the average 2‐terminal reliability (A2TR) against a set of critical node failures and the critical nodes are the ones that minimize the A2TR of the network. So, the design/upgrade problem is a bi‐level max‐min optimization problem. Recently, a multi start greedy randomized heuristic was proposed for both problems. Here, we propose an alternative method based on a greedy deterministic algorithm and we provide computational results showing that the new method obtains better solutions. The results show that the resiliency difference between existing network topologies and the best network design solutions is very high but this difference can be significantly reduced by network upgrades with small fiber length budgets.